Overlooked muscle cramps in patients with chronic liver disease: in relation to the prevalence of muscle cramps. Issue 3 (March 2019) - Murata, Ai; Hyogo, Hideyuki; Nonaka, Michihiro; Sumioka, Akihiko; Suehiro, Yosuke; Furudoi, Akira; Fujimoto, Yoshifumi; Aisaka, Yasuyuki; Komatsu, Hironao; Tokumo, Hironori
Abstract : Introduction: Muscle cramps are common comorbidities in chronic liver disease (CLD). Although the prevalence of these has been reported in patients with liver cirrhosis (LC), that of CLD is unknown. In this study, we aimed to clarify the prevalence and characteristics of muscle cramps in individual CLD. Patients and methods: A total of 432 patients with CLD who visited our hospital were enrolled. The existence of muscle cramps, frequency, time zone, duration, and the degree of pain were investigated using a medical interview questionnaire. Results: The median age of the patients was 65 years and 48.6% of the patients were women. The prevalence of muscle cramps was 25.9%. Age, female sex, lower BMI, existence of comorbid diseases, and liver fibrosis were associated significantly with muscle cramps. In LC, muscle cramps were significantly frequent, and the severity and duration of these were significantly stronger and longer compared with chronic hepatitis. Female sex [odds ratio (OR): 2.26; P =0.014], diabetes (OR: 29.4; P <0.001), chronic kidney disease (OR: 8.33; P =0.004), and lower BMI (OR: 0.853; P <0.001) were independent factors associated with muscle cramps in CLD. Muscle mass indices were significantly lower among nonalcoholic fatty liver disease patients with muscle cramps, female patients, elderly patients, and patients with advanced fibrosis. Conclusion: The prevalence of muscle cramps was relatively high in CLD. Female sex, comorbid diabetes, and chronic kidney disease are associated with muscle cramps in CLD. Furthermore, reduced muscle mass is related to muscle cramps in nonalcoholic fatty liver disease.